2021
DOI: 10.1002/cjoc.202100289
|View full text |Cite
|
Sign up to set email alerts
|

Ethoxylation of Phenols Catalyzed by Metal‐Free Lewis Pairs: Living/Controlled Polymerization in a Slow‐Initiation Mode

Abstract: Main observation and conclusion Phenols, instead of conventional alcoholic compounds, are used to initiate ring‐opening polymerization (ROP) of ethylene oxide and propylene oxide in bulk at room temperature in cooperation with the recently prevailing bicomponent metal‐free catalyst comprising an organobase and triethylborane. Experimental and DFT calculation results both point out that due to the lower nucleophilicity of the initiating (phenolate) species than the propagating (alcoholate) species, chain initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Organoboron-catalyzed anionic ROP/ROCOP follows an immortal manner in that chain transfer is much faster than propagation. Successful examples demonstrated that phenols, 287 alcohols, 233,241 carboxylic acids, 288 and carboxylate salts 180,286 were all effective chain transfer agents. Therefore, well-defined star and block polymers could be directly synthesized when multifunctional chain transfer agents or macromolecular chain transfer agents 289 were used.…”
Section: Organoboron Mediated Ionic Ropmentioning
confidence: 99%
“…Organoboron-catalyzed anionic ROP/ROCOP follows an immortal manner in that chain transfer is much faster than propagation. Successful examples demonstrated that phenols, 287 alcohols, 233,241 carboxylic acids, 288 and carboxylate salts 180,286 were all effective chain transfer agents. Therefore, well-defined star and block polymers could be directly synthesized when multifunctional chain transfer agents or macromolecular chain transfer agents 289 were used.…”
Section: Organoboron Mediated Ionic Ropmentioning
confidence: 99%
“…Hydroxyl compounds have been the most commonly used initiators in the ROP of epoxides, resulting in aliphatic ether α-end junctions and main-chain monomeric units that are difficult to selectively cleave or modify. Therefore, significant efforts have been dedicated to expanding the structural diversity and the heterofunctional initiators for ROP of epoxides, including amide, , carboxylic acid, , phenols, and carbamates . Furthermore, the nonalcoholic initiator-mediated-controlled ROP of epoxides will contribute to the advancement of novel functionalities in polyethers and their derivatives, thereby providing enhanced opportunities for selective cleavage/modification of the initiating moieties.…”
Section: Introductionmentioning
confidence: 99%